Avaliação dos efeitos do ativador da enzima conversora de Angiotensina 2 (DIZE) na pressão arterial de ratos - Marilda Luz de Andrade de Maria (2011)
Traditionally, the Renin-Angiotensin System (RAS) is considered an endocrine system formed by enzymatic pathways and it plays an important role in the cardiovascular function. Nowadays, new components such as the heptapeptide angiotensin-(1-7) [Ang-(1-7)] have been added to this system. Angiotensin-converting enzyme (ACE) 2 is the main Ang-(1-7)-forming enzyme and it is important to maintain the balance of the RAS. Previous studies have shown that the activation of endogenous ACE2 using the compound XNT results in several beneficial effects in the cardiovascular system. Recently, a second ACE2 activator was described, the diminazene aceturate (DIZE), which has better physical and chemical properties. Thus, the objective of this study was to evaluate the effects of DIZE on blood pressure (BP) and heart rate (HR) of rats and to analyze the mechanisms of action by which this compound changes these parameters. Also, we analyzed the effects of DIZE on arterioles from the mesenteric vascular bed using the Intravital Microscopy technique. Male Wistar rats (200-300g) underwent surgeries for implantation of cannulas into the femoral artery for recording BP and HR and into the femoral vein for the injection of increasing doses of DIZE (0.5, 5, 10, 20mg/kg) and RAS inhibitors and blockers. This experiments were performed in awake rats 24 h after the surgery. The results showed that DIZE causes a dose-dependent reduction in BP accompanied by increase in HR. In order its mechanisms of action, additional groups of rats were pre-treated with the Mas receptor antagonist A-779 (10nmol/kg, i.v.), the nitric oxide (NO) synthase inhibitor L-NAME (10mg/kg, i.v.), the prostaglandins inhibitor Indomethacin (10mg/kg, i.v.), the ACE inhibitor Captopril (10mg/kg, i.v.) or the AT1 receptor antagonist Losartan (1mg/kg, i.v.) 15 min before the administration of DIZE (5mg/kg). The results showed that A-779, L-NAME, Indomethacin, Captopril and Losartan do not block the effects of DIZE on BP and HR. Finally, the Intravital Microscopy results revealed that DIZE causes a decrease in blood flow of arterioles of the mesenteric vascular bed without significant changes in the arteriolar diameters. Therefore, our results indicated that DIZE is a potent hypotensive compound and this effect is independent of Mas and AT1 receptors, ACE, NO release and prostaglandin synthesis.